Development of DC DVR Device Based on Super Capacitor Energy Storage - YIN Huchen; LIN Shaobo; LIU Jianwei; HAN Minxiao; LI Wentao (Kongzhi Yu Xinxi Jishu)
Voltage sag is one of the most hazardous power quality problems in power system. This paper proposes a novel DC DVR device based on super-capacitor, presents the main circuit and the control method of super capacitor charging and discharging. Simulated and experimental results show that the device can effectively support the sensitive load by keeping the DC voltage stable in the event of voltage sag, which will reduces the sag’s impact on sensitive loads.